1982
DOI: 10.5479/si.00775630.256.1
|View full text |Cite
|
Sign up to set email alerts
|

Cays of the Belize Barrier Reef and Lagoon

Abstract: Sand c a y s of t h e n o r t h e r n b a r r i e r r e e f 9 S t George's E a s t Cay Paunch Cay S e r g e a n t ' s Cay Curlew CayGo£ f ' s Cay Cays o f t h e b a r r i e r r e e f lagoon A. S e a l Cay E n g l i s h Cay Sandbore s o u t h of E n g l i s h CayThe n o r t h e r n lagoon Ambergris Cay Cay Caulker Cay Chapel S t George ' s CayCays between Cay Chapel and B e l i z e ~o h o c a y S t a k e Bank S p a n i s h Lookout Cay Water Cay B.The Southern T r i a n g l e sRobinson P o i n t Cay Robinson I s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…In both instances the islands migrated lagoonward on their reef platforms. These observations are consistent with those of Stoddart et al (1982) who suggested that reef islands in Belize also displayed lagoonward migration in response to rising sea level.…”
Section: Change In Boundary Conditions: Sea Level and Climatesupporting
confidence: 94%
See 1 more Smart Citation
“…In both instances the islands migrated lagoonward on their reef platforms. These observations are consistent with those of Stoddart et al (1982) who suggested that reef islands in Belize also displayed lagoonward migration in response to rising sea level.…”
Section: Change In Boundary Conditions: Sea Level and Climatesupporting
confidence: 94%
“…Umbgrove (1947) and Verstappen (1954) were the first to develop a causal relationship between climate and reef island behaviour invoking medium-term (decadal) shifts in prevailing wind direction and strength and its influence on wave energy as a control on morphological adjustment of islands in Djakarta Bay, Indonesia. Flood (1986) also related decadal changes in wind to progressive shifts in reef island planform in the Great Barrier Reef whereas, Stoddart et al (1982) found that decadal change on islands within the Belize barrier reef system resulted from hurricane activity. There are a number of conspicuous features of these medium-term studies that are relevant to the issue of future island change.…”
Section: Introductionmentioning
confidence: 93%
“…The mangroves Rhizophora mangle L., Avicennia germinans (L.) Stearn, Laguncularia racemo.sa (L.) Gaertn. f., and Conocalpus erectus L. (taxonomy follows Tomlinson, 1986) are found along rivers, in estuaries, and on numerous mangrove cays in the lagoon shoreward of the barrier reef (Hartshorn et al, 1984;Stoddart et al, 1982). All four species cooccur from HHW to mean water (MW).…”
Section: Study Sitesmentioning
confidence: 99%
“…1) were also surveyed to obtain an estimate of variability in herbivory levels among LW mangrove trees on the mainland. The 2 50-km-long barrier reef complex off the coast of Belize is the largest continuous reef in the Caribbean Sea (Stoddart et al 1982). Numerous cays dominated by Rhizophora occur between the reef and mainland.…”
Section: Introductionmentioning
confidence: 99%